2011
DOI: 10.3168/jds.2010-3729
|View full text |Cite
|
Sign up to set email alerts
|

Short communication: Effect of a stable pen management strategy for precalving cows on dry matter intake, plasma nonesterified fatty acid levels, and milk production

Abstract: During the close-up transition period, dairy cows are at risk for negative energy balance due to increasing energy demands and decreasing feed intake. This can result in postparturient health problems and decreased milk production after calving. Cows are frequently regrouped during this period, which can negatively affect feeding and resting behavior. The hypothesis was that housing in a stable pen during the close-up transition period should result in a more settled environment resulting in fewer displacement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…In contrast, Silva et al (2013) found that regrouping cows weekly did not affect NEFA or BHB compared with stable groups before calving. Similarly, Coonen et al (2011) found no effect of twice-weekly regroupings before calving on NEFA compared with stable groups. Least squares means (±SE) of the number of actor and reactor replacements for groups (n = 8/treatment) during a baseline period (5 wk before calving) and when dairy cows were housed in either an unpredictable and competitive, or a predictable and noncompetitive social environment in the 4 wk before calving.…”
Section: Discussionmentioning
confidence: 91%
“…In contrast, Silva et al (2013) found that regrouping cows weekly did not affect NEFA or BHB compared with stable groups before calving. Similarly, Coonen et al (2011) found no effect of twice-weekly regroupings before calving on NEFA compared with stable groups. Least squares means (±SE) of the number of actor and reactor replacements for groups (n = 8/treatment) during a baseline period (5 wk before calving) and when dairy cows were housed in either an unpredictable and competitive, or a predictable and noncompetitive social environment in the 4 wk before calving.…”
Section: Discussionmentioning
confidence: 91%
“…During the transition period, dairy cows are in a state of great metabolic stress because of the increased demand for nutrients to maintain fetal growth and milk synthesis. Transition dairy cows tend to have negative energy and amino acid balance after calving, which leads to an increase in fat and protein mobilization in tissues [1,2]. A negative methyl donor balance also likely occurs in transition cows because milk is high in methylated compounds [3].…”
Section: Introductionmentioning
confidence: 99%
“…* denotes significant differences between treatments (P < 0.05) within week; † denotes a tendency between treatments (P = 0.054) within week. pen management did not find a difference in feed bunk displacements for prepartum cows (Coonen et al, 2011). Those researchers speculated that minimal disruption would occur with only a small number of animals moving into the dynamic pen.…”
Section: Figurementioning
confidence: 97%
“…At times, pens will be underused while a few remaining cows await parturition. A study that examined stable pen management versus a dynamic pen did not find a difference in the number of displacements from the feed bunk, DMI, plasma NEFA concentrations, and milk production up to 30 DIM (Coonen et al, 2011). In that study, approximately 1 cow was added at a time to a small pen with only 10 cows.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation